Legal Consequences Derived from the Violation of Exit Labor Stability by the Employer - Puntriano Rosas, César Alfredo (2016)
After a conceptual overview of the scope of the right to job stability, its relationship with other rights (right to work, right to access to employment, right to maintain employment) and its constitutional, international and legal regulation and the position of jurisprudence, the author goes on to discuss the complex picture presented to the employer before a decision to dismiss both from a legal perspective (compensation, replacement) and case law (damages, replacement) adding a paragraph called “others” the recount administrative consequences arising from said measure both labor (SUNAFIL) and tax (SUNAT) viewpoint.